Nanoplasmonics tuned "click chemistry". Issue 13 (10th March 2016) - Tijunelyte, I.; Guenin, E.; Lidgi-Guigui, N.; Colas, F.; Ibrahim, J.; Toury, T.; Lamy de la Chapelle, M.
Abstract : We demonstrate that the thiol–ene "click" reaction is locally induced at the surface of gold nanoparticles by exploiting their nanoplasmonic properties. Abstract : Nanoplasmonics is a growing field of optical condensed matter science dedicated to optical phenomena at the nanoscale level in metal systems. Extensive research on noble metallic nanoparticles (NPs) has emerged within the last two decades due to their ability to keep the optical energy concentrated in the vicinity of NPs, in particular, the ability to create optical near-field enhancement followed by heat generation. We have exploited these properties in order to induce a localised "click" reaction in the vicinity of gold nanostructures under unfavourable experimental conditions. We demonstrate that this reaction can be controlled by the plasmonic properties of the nanostructures and we propose two physical mechanisms to interpret the observed plasmonic tuning of the "click" chemistry.